Public Expenditure on Capital Formation and Private Sector Productivity Growth: Evidence From Lithuania and the Euro Area - Žemgulienė, Jolanta (Organizations and Markets in Emerging Economies, 2012)
This paper explores a relationship between government expenditure on fixed capital formation and private sector productivity in Lithuania and Euro area economies. The extent to which variations of productivity in private Lithuanian economy can be explained by the flow of government expenditure on gross capital formation is estimated from regression analysis based on Cobb-Douglas production function approach. Quarterly state-level data from Lithuania and pooled data from the Euro area countries (12 countries) for the period of 2000 – 2010 were used. The regression estimation indicates the insignificant result for the impact of volume of government expenditure on fixed capital formation on the private sector output growth. Empirical analysis also revealed the negative significant result for the government expenditure on fixed capital formation as a share of GDPfor both the Lithuania and Euro area countries.